2007
DOI: 10.1248/bpb.30.1826
|View full text |Cite
|
Sign up to set email alerts
|

Production and Regulation of Eotaxin-2/CCL24 in a Differentiated Human Leukemic Cell Line, HT93

Abstract: When a human leukemic cell line, HT93 was incubated with all-trans retinoic acid (ATRA), IL-5, or both, this cell line was differentiated into eosinophic lineage, in that an eosinophilic specific granule proteins, major basic protein (MBP) and eosinophil peroxidase (EPO) appeared. Both CD11b and CC chemokine receptor, CCR3 expression were upregulated, while CD71 expression was downregulated by ATRA or ATRA؉IL-5. Concomitantly, marked production of eotaxin-2/CCL24 was observed, but no production of eotaxin-1/CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…If reduced expression of chemokines contributes to immune evasion by colorectal cancer, modulation of chemokine expression in cancer cells could be a possible target for anticancer therapies as well as a prognostic factor for colorectal cancer [ 31 , 32 ]. As some studies on leukemia and CCL24 have suggested, specific kinds of chemokines might affect the migration of specific types of eosinophils in colorectal cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…If reduced expression of chemokines contributes to immune evasion by colorectal cancer, modulation of chemokine expression in cancer cells could be a possible target for anticancer therapies as well as a prognostic factor for colorectal cancer [ 31 , 32 ]. As some studies on leukemia and CCL24 have suggested, specific kinds of chemokines might affect the migration of specific types of eosinophils in colorectal cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of CCL24 is likely to involve specific transcription factors such as Smad3 and GATA-1. CCL24 was increased in the skin of Smad3-/- mice [ 51 ] and in the GATA-1-overexpressed human leukemic HT93 cell line [ 52 ]. Although TNF induced CCL24 protein in epithelial cells of nasal polyps [ 53 ], it had no effect in SKOV-3 cells [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Displayed in our study negative feedback between the expression of eotaxin-2 mRNA and IL-2 and IL-4 may be explained cross-regulation between chemokines and cytokines. Yoshida et al [14] observed that IL-5 does not alter the expression of CCR3 and eotaxin-2 cell line NT93. We found that in healthy volunteers between the expression of eotaxin-2 mRNA and IL-5 production is a negative correlation, which can be attributed to suppressive influence of the Th2 immune response to eotaxin-2.…”
Section: Discussionmentioning
confidence: 98%